Visual and Computational Plasma Physics - Hsu, James Jang-Yu (Singapore: World Scientific, 2015)
This book contains Matlab programs to demonstrate the numerical algorithms, the analytical approaches, and the physical principles. It starts with single particle, single fluid, and single wave, then the kinetic theory, the transport, the magnetohydrodynamics, and the nonlinear physics. The book emphasizes on the numerical algorithm and the analytical asymptology to tackle problems in plasma physics, and to demonstrate the underlying physics principles by graphical visualization. Students are introduced to the multiple time and multiple space scales as they learn the basic plasma phenomena, and are requested to solve problems with either Matlab or C++. This book is targetting at the senior and graduate level. The emphasis of this book is to teach students to solve problems from the features and characteristics of the problem itself. It provides the students for the most important learning that is not knowing the solution, but knowing how to figure out the solution.
Bibliography 405-410p.; Index 415-418p.
Keywords: Numerical algorithms; Single fulid; Plasma transport